Honouring stories of losers: using cinema to show students the dark side of neoliberalism - Bobbo, Natascia (Studi sulla Formazione/Open Journal of Education, 2024)
Teaching work pedagogy should mean giving university students the competences to assess the quality of the choices already made in the training of young people for work, and to design and implement training paths that are more and more capable of contributing to the building of a democratic and equal society. This sentence has its roots in almost three theories: Van Manen's concept of pedagogy as a set of reflections to assess the quality of past educational experiences and to better plan new ones: Pratt's perspective of education as a form of social reform , and Adorno's concept of democracy as the only social project in which men and women can become human. The chosen of these theoretical perspectives are convenient to the critical pedagogy approach, which highlights the reflections of this contribution that aims to present a didactic experience in a university class of work pedagogy realised by the means of a film. “Daniel Black” by Ken Loach was chosen as the film best able to honour the losers of our neo-liberal society and, in the meantime, make students aware of their limits and strengths in conceiving the complexity of the market logic.